Professional leadership of Chinese university teachers: an empirical exploration of multiple related factors and self-efficacy's role - Yin, Weiwei; Zhang, Guowei (Frontiers in Psychology, 2025)
IntroductionHigher education, as the core of talent development and knowledge innovation, relies greatly on the comprehensive capabilities of university teachers, among which professional leadership is vital for the connotative development of universities. Although scholars have researched influencing factors such as individual traits and organizational environment, there are critical gaps in existing studies. This study, set in Chinese universities and based on the Social Cognitive Theory, aims to empirically explore the relationships between Chinese university teachers' personal qualities, school cultural characteristics, and professional leadership.MethodsThrough an exhaustive literature review, seven hypotheses were proposed. A quantitative approach was adopted, data were collected via questionnaires, a structural equation model was established, and data were analyzed using SPSS and Amos.ResultsThe results indicate that personal qualities, school cultural characteristics, and self-efficacy are significantly related to professional leadership, with self-efficacy playing a mediating role. A “dual antecedents-single mediator-single outcome” influence path was identified: the two antecedents directly affect professional leadership, and self-efficacy serves as the core bridge.DiscussionThese three factors are crucial for cultivating leadership competencies and institutional advancement. The finding emphasizes the irreplaceability of self-efficacy, breaks the limitation of traditional studies that only focus on the direct impact of personal qualities and school cultural characteristics, and provides key insights into transforming potential conditions into actual leadership behaviors.